Complexity in Multilingualism (Research). Issue 1 (6th August 2020) - Beisbart, Claus
Abstract: Does complexity make multilingualism special? Since there is no unequivocal notion of complexity on which researchers agree, several characteristics that have been considered crucial for complexity are brought to bear on multilingualism. While multilingualism is fairly complex in some senses, for instance, because it requires that many variables be studied, it is less clear whether multilingualism becomes special in this way. The most salient possible way in which multilingualism might be special due to its complexity is that qualitatively new features emerge as we move from mono‐ or bilingualism to multilingualism. While research in mathematics and physics has shown examples in which novel features emerge at a certain level, related results are not easily transferred to multilingualism. This is shown by analyzing the application of dynamic systems theory to multilingualism by Herdina and Jessner. It is ultimately a matter of empirical research whether there are suitable novel features that make multilingualism special. Abstract :